The Zebrafish as an Emerging Model to Study DNA Damage in Aging, Cancer and Other Diseases - Cayuela, Maria Luisa; Claes, Kathleen B. M.; Ferreira, Miguel Godinho; Henriques, Catarina Martins; van Eeden, Fredericus; Varga, Máté; Vierstraete, Jeroen; Mione, Maria Caterina (Frontiers in Cell and Developmental Biology, 2019)
Cancer is a disease of the elderly, and old age is its largest risk factor. With age, DNA damage accumulates continuously, increasing the chance of malignant transformation. The zebrafish has emerged as an important vertebrate model to study these processes. Key mechanisms such as DNA damage responses and cellular senescence can be studied in zebrafish throughout its life course. In addition, the zebrafish is becoming an important resource to study telomere biology in aging, regeneration and cancer. Here we review some of the tools and resources that zebrafish researchers have developed and discuss their potential use in the study of DNA damage, cancer and aging related diseases.